2012
DOI: 10.1534/genetics.112.141200
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent A-to-I RNA Editing in Rat Cortical Neurons

Abstract: Changes in neural activity influence synaptic plasticity/scaling, gene expression, and epigenetic modifications. We present the first evidence that short-term and persistent changes in neural activity can alter adenosine-to-inosine (A-to-I) RNA editing, a posttranscriptional site-specific modification found in several neuron-specific transcripts. In rat cortical neuron cultures, activity-dependent changes in A-to-I RNA editing in coding exons are present after 6 hr of high potassium depolarization but not afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 51 publications
6
37
0
Order By: Relevance
“…Indeed, a similar increasing editing pattern is reported in Drosophila at several genes 40 . We also note that several sites with increasing editing patterns have previously been shown to be edited in an activity-dependent manner 41,42 , which is further evidence for functionality. In addition, while we found that the increasing editing pattern was evolutionarily conserved, our results with post-mortem and in vitro human samples enabled us to identify developmentally regulated RNA editing sites not found in other model organisms.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, a similar increasing editing pattern is reported in Drosophila at several genes 40 . We also note that several sites with increasing editing patterns have previously been shown to be edited in an activity-dependent manner 41,42 , which is further evidence for functionality. In addition, while we found that the increasing editing pattern was evolutionarily conserved, our results with post-mortem and in vitro human samples enabled us to identify developmentally regulated RNA editing sites not found in other model organisms.…”
Section: Discussionsupporting
confidence: 64%
“…However, RNA-seq is generally less accurate in quantifying RNA editing levels due to the moderate read coverage currently available (Ramaswami et al 2013). Several attempts have been made to couple targeted amplification and next-generation sequencing for accurate quantification of RNA editing with limited success (Li et al 2009;Sanjana et al 2012;Ramaswami et al 2013). Very recently, a more robust experimental system which combines microfluidics-based multiplex PCR has been presented by Zhang et al (2014).…”
Section: Resultsmentioning
confidence: 99%
“…This may be important not only for neuronal development but also for neuronal plasticity. Indeed, acute and chronic neuronal activation of both hippocampal and cortical neurons alters the editing of several substrates Sanjana et al, 2012). However, differences in nuclear concentration of ADAR2 upon neuronal activation remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%